German Real Estate Funds – Changes in Return Distributions and Portfolio Favourability - Michael Stein (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Since 2008, the German open-ended real estate fund (GOEREF) industry has experienced a critical phase of suspensions of redemption of fund shares, announced fund terminations and, eventually, introduction of a new regulation. With assets under management of over EUR 80 billion, GOEREFs are the dominant indirect real estate investment vehicle in Germany. Thus, it is extremely important to study the effects of this crisis on the risk and return characteristics of the respective funds. Both net asset values (NAVs) and potential secondary market prices of the shares of funds with suspended redemptions are used. The resulting total return patterns are analysed on an index basis for fund groups that best represent the most important investor groups for GOEREFs. Groups that comprised a higher number of funds with suspended redemptions were considerably worse off and less attractive in an asset allocation context than the others given the often much lower secondary market prices. However, changes in return and risk must also be considered in terms of NAVs. The fund group comprising co-operative savings banks' funds was virtually unaffected by the liquidity crisis and continued to be deliver stable and non-volatile returns, while the other fund groups exhibited a clear shift in their respective return profiles.
Keywords: G01; G10; G12; 330; German real estate funds; return distributions; portfolio building; secondary market